Contribution of Genetic Polymorphisms of Inflammation Response Genes on Sporadic Colorectal Cancer Predisposition Risk in Malaysian Patients – A Case Control Study - Mohd Aminudin, Mustapha; Ankathil, Ravindran; Ahmad Aizat, Abdul Aziz; Siti Nurfatimah, Mohd Shahpudin; Andee Dzulkarnaen, Zakaria; Muhammad Radzi, Abu Hassan; Kamarul Imran, Musa (West Asia Organization for Cancer Prevention (WAOCP), 2019)
AIM: To investigate the frequencies and association of polymorphic genotypes of IL-8 -251 T>A, TNF-α -308 G>A, ICAM-1 K469E, ICAM-1 R241G, IL-6 -174 G>C, and PPAR-γ 34 C>G in modulating susceptibility risk in Malaysian colorectal cancer (CRC) patients. Methods: In this case-control study, peripheral blood samples of 560 study subjects (280 CRC patients and 280 controls) were collected, DNA extracted and genotyped using PCR-RFLP and Allele Specific PCR. The association between polymorphic genotype and CRC susceptibility risk was determined using Logistic Regression analysis deriving Odds ratio (OR) and 95% CI. Results: On comparing the frequencies of genotypes of all single nucleotide polymorphisms ( SNPs ) in patients and controls, the homozygous variant genotypes IL-8 -251 AA and TNF-α -308 AA and variant A alleles were significantly higher in CRC patients. Investigation on the association of the variant alleles and genotypes singly, with susceptibility risk showed the homozygous variant A alleles and genotypes IL-8 -251 AA and TNF-α -308 AA to be at higher risk for CRC predisposition. Analysis based on age, gender and smoking habits showed that the polymorphisms IL8 -251 T>A and TNF – α 308 G>A contribute to a significantly higher risk among male and female who are more than 50 years and for smokers in this population. Conclusion: We observed an association between variant allele and genotypes of IL-8-251 T>A and TNF-α-308 G>A polymorphisms and CRC susceptibility risk in Malaysian patients. These two SNPs in inflammatory response genes which undoubtedly contribute to individual risks to CRC susceptibility may be considered as potential genetic predisposition factors for CRC in Malaysian population.